Mechanism-based subtyping in binge eating: understanding neurobehavioral heterogeneity across negative emotionality, approach behavior, and executive function - Leyla R. Brucar; Eric Rawls; Ann F. Haynos; Carol B. Peterson; Anna Zilverstand (Translational Psychiatry)
Abstract Binge eating (BE), a transdiagnostic feature that occurs across eating disorders and in the general population, carries significant health risks even in the absence of a full-syndrome diagnosis. The limited efficacy of current treatments for binge-type eating disorders highlights the need to better understand the mechanistic heterogeneity underlying BE to optimize treatment allocation, advance personalized medicine, and ultimately improve outcomes. We hypothesized considerable heterogeneity within three neurofunctional domains prevalent across compulsive behaviors and implicated in BE: approach-related behavior, executive function, and negative emotionality. We analyzed data from 612 participants (ages 18–59, 66% female) from the enhanced Nathan Kline Institute-Rockland Sample, including 461 controls and 151 individuals with BE behaviors. Using data-driven statistical modeling of comprehensive, multimodal measures across the three hypothesized domains, we identified subtypes of BE. Subtypes were validated using assessments of eating pathology, substance use, clinical diagnostics, and resting-state functional magnetic resonance imaging. Three distinct and stable subtypes emerged: a ‘Negative Emotionality’ subtype characterized by greater negative affect, emotion dysregulation and psychiatric comorbidity, an ‘Approach’ subtype with higher approach-related and impulsive behaviors, and a ‘Restrained’ subtype that was overcontrolled and harm avoidant. The Approach and Restrained subtypes further demonstrated unique neurobiological profiles, as determined by graph theory analysis of resting-state functional connectivity. All subtypes showed similar proportions of BE episodes meeting clinical-level threshold (≥4 objective binge episodes/month), and no differences in BMI, indicating functionally distinct expressions of BE, beyond clinical severity and diagnostic classification. This study is the first to explore the mechanistic heterogeneity of BE through a comprehensive multi-modal assessment across three neurofunctional domains in a single sample. Findings highlight the need for updated models of BE etiology that integrate approach/reward-related behaviors, impulsivity and overcontrolled behaviors, and negative emotionality, and suggest the potential of these functionally-derived subtypes to inform the development of personalized, targeted interventions.